Biosensors - Evtugyn, Gennady (Springer Berlin / Heidelberg, 2013)
Covering all the essentials from biochemical recognition to the latest MEMS systems, this book on biosensors and their applications includes a wealth of case studies. Written by a leading expert on the subject, it includes a chapter on likely future advances.